Dynamic environment at the Zr6 oxo cluster surface is key for the catalytic formation of amide bonds. Issue 1 (22nd November 2022) - Zhang, Yujie; Kokculer, Ismail Y.; de Azambuja, Francisco; Parac-Vogt, Tatjana N.
Abstract : Catalytic formation of amide bonds by a discrete Zr6 O8 cluster reveals a dynamic environment on the cluster surface, providing key molecular insights on its intrinsic reactivity for the design of cluster-based and MOF catalysts. Abstract : Zirconium compounds are an attractive alternative to costly, low abundant metals for the development of inexpensive, readily available, and robust catalysts. The air and moisture stable Zr oxo clusters such as the Zr6 O8 species, are of particular interest as they are key building blocks of several Zr-based metal–organic framework (Zr-MOF) catalysts. However, broader use of these cluster-based materials as catalysts is still hampered by the modest understanding of their fundamental reactivity. To bridge this gap, we report on the activity of a soluble Zr6 O8 cluster, [Zr6 (OH)4 O4 (OMc)12 ] (OMc = methacrylate) (Zr 6 ), as a discrete molecular catalyst for the atom-economic formation of amide bonds. This reaction demands two completely different substrates interacting with the Zr 6 catalyst, a key step rarely addressed in MOF catalyzed reactions. Remarkably, Zr 6 catalyzes the formation of amide bonds directly from non-activated carboxylic acid and amine substrates in ethanol, without requiring anhydrous conditions or water scavenging to achieve good yields. As shown by a series of kinetic, and mechanistic experiments, this promising reactivity arises from a dynamic environment at the cluster surface, where the essential coordination of both substrates requires an excess of amine to enhance the reaction output. Strikingly, Zr 6 catalyst tolerates a range of substrates, including (hetero)aromatic, aliphatic, and α-branched acids, even though their nature directly impacts the reaction efficiency. Further, insights for the future design of catalysts based on Zr oxo cluster are discussed through a detailed comparison of Zr 6 reactivity with a related Zr 12 cluster, and Zr-MOF catalysts. Considering the advantages of zirconium, and the relevance of discrete Zr oxo clusters as building blocks of several MOF materials of varied utility, the molecular level understanding disclosed here contributes at large to the development of novel catalytic entities, and sustainable approaches to synthetic chemistry.